2018
DOI: 10.3174/ajnr.a5513
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Extravasation Quantification on Dual-Energy CT of the Brain Performed after Mechanical Thrombectomy for Acute Ischemic Stroke Can Predict Hemorrhagic Complications

Abstract: The presence of parenchymal hyperdensity with a maximum iodine concentration of >1.35 mg/mL may identify patients developing intracerebral hemorrhage with 100% sensitivity and 67.6% specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 31 publications
0
42
1
Order By: Relevance
“…The former finding is similar to the report from Almqvist et al's ( 7 ) study of DECT. The latter finding of pure contrast staining proportion is higher than in three previously published studies of a post-interventional DECT strategy within 30, 60, or 120 min (68, 47, and 32%, respectively) ( 8 , 13 , 14 ).…”
Section: Discussioncontrasting
confidence: 59%
“…The former finding is similar to the report from Almqvist et al's ( 7 ) study of DECT. The latter finding of pure contrast staining proportion is higher than in three previously published studies of a post-interventional DECT strategy within 30, 60, or 120 min (68, 47, and 32%, respectively) ( 8 , 13 , 14 ).…”
Section: Discussioncontrasting
confidence: 59%
“…Bonatti et al showed that parenchymal hyperdensity with absolute maximum iodine concentration of >1.35mg/mL measured with three-material iodine quantification techniques could predict hemorrhagic complication with 100% sensitivity and 68% specificity. 37 A subsequent study showed that the relative percentage of iodine concentration within parenchymal hyperdensity compared to the superior sagittal sinus within one-hour post-EVT may be a more reliable biomarker of hemorrhage development than maximum iodine concentration. This method was thought to account for variability in iodine concentration depending on factors such as patient size, cardiac output, renal function, and volume of contrast medium administered.…”
Section: Ischemic Strokementioning
confidence: 99%
“…These studies suggest that the presence or amount of contrast staining after EST may have predictive value for the clinical outcome. However, in some studies, clinical parameters were not considered and follow-up imaging was inconsistent with regard to time interval and imaging method [38][39][40].…”
Section: Prediction Of Infarction Development or Future Hemorrhagic Tmentioning
confidence: 99%